Physical and Electrochemical Characterization of the Photochemically Growth of Silver Nanoplates on Graphene Oxide. - Lasso López, Esteban David (2020)
Recently, Graphene Oxide (GO) has attracted considerable attention for various applications involved in electrochemical systems and as a support material for several metallic nanoparticles. In this work, we report the photochemical growth of silver nanoplates on graphene oxide (GO) by the use of a In- situ and Ex-situ method. The synthesis of Triangular Silver Nanoplates (T-SNPs) on GO was made by using a modified photochemical-reduction method at different irradiation wavelengths (440, 540, 650, and 200-600 nm). T SNPs/GO nanocomposite was characterized using: Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Raman spectroscopy, UV-vis spectroscopy, and Cyclic Voltammetry (CV). It was found that plasmonic bands of T-SNPs can be tuned using specific light wavelengths regardless of the presence of GO in the solution. Also, silver nanoplates were formed and deposited on GO for both methodologies. We have also found that the In-situ method promotes a narrow size distribution of silver nanoplates. Raman analysis shows an increase in the Raman signal due to the presence of silver and In-situ synthesis reveals to introduce more defects to the GO surface (ID/IG ratio). The electrochemical deposition of T-SNPs to a graphite micro-electrode increase the conductivity and overall, the silver nanoplates prepared by the In-situ method give a higher current on average, especially the ones that were grown by a light source of 540 nm wavelength.